Sensory contributions to stabilization of trunk posture in the sagittal plane - van Dieën, Jaap H.; van Drunen, Paul; Happee, Riender (Journal of biomechanics, 2018)
Trunk stabilization is required to control posture and movement during daily activities. Various sensory modalities, such as muscle spindles, Golgi tendon organs and the vestibular system, might contribute to trunk stabilization and our aim was to assess the contribution of these modalities to trunk stabilization. In 35 healthy subjects, upper-body sway was evoked by continuous unpredictable, force-controlled perturbations to the trunk in the anterior direction. Subjects were instructed to either ‘maximally resist the perturbation’ or to ‘relax but remain upright’ with eyes closed. Frequency response functions (FRFs) of admittance, the amount of movement per unit of force applied, and reflexes, the modulation of trunk extensor activity per unit of trunk displacement, were obtained. To these FRFs, we fitted physiological models, to estimate intrinsic trunk stiffness and damping, as well as feedback gains and delays. The different model versions were compared to assess which feedback loops contribute to trunk stabilization. Intrinsic stiffness and damping and muscle spindle (short-delay) feedback alone were sufficient to accurately describe trunk stabilization, but only with unrealistically low reflex delays. Addition of muscle spindle acceleration feedback or inhibitory Golgi tendon organ feedback yielded realistic delays and improved the model fit, with a significantly better model fit with acceleration feedback. Addition of vestibular feedback did not improve the model fit. In conclusion, muscle spindle feedback and intrinsic mechanical properties are sufficient to describe trunk stabilization in the sagittal plane under small mechanical perturbations, provided that muscle spindles encode acceleration in addition to velocity and position information.